Optimised formulation and characterisation of oregano essential oil edible composite films by response surface methodology - Hekun Duan; Zitian Yuan; Suyan Liu; Liang Jin; Ping Wen; Yaqi Wang; Fuhao Hu; Fei Han (Czech Journal of Food Sciences, 2024)
The objective of this research is to prepare a composite packaging film by integrating oregano essential oil (OEO) into a chitosan (CS)/polyvinyl alcohol (PVA) matrix to enhance the preservative properties of food packaging films. For this purpose, the study established multiple quality evaluation methods for composite films. The composite weights for each evaluation indicator were calculated through the analytic hierarchy process-coefficient of variation (AHP-CV), deriving the comprehensive score value (OD). Employing OD as the ultimate evaluation indicator, the optimal preparation formula for the OEO composite film was ascertained by applying response surface methodology (RSM), incorporating insights gained from single-factor experiments. The results showed that the optimum formulation was CS 1.51 g, PVA 3.51 g, glycerin 1.97 g, and Tween-80 0.51 g. The OD for the OEO composite film prepared under these conditions was 83.95 ± 0.12%, closely matching the predicted value of 83.91%. Characterisation further confirmed the cross-linking action between CS and PVA, while the inclusion of OEO enhanced the antimicrobial activity of the composite film. These findings suggest incorporating OEO into composite packaging films holds considerable potential for enhancing food packaging applications.